Peningkatan Kualitas Rumah Tinggal, Sarana, dan Prasarana Permukiman Tepi Air Cikoang Berbasis Kebutuhan dan Partisipasi Masyarakat - Afifah - Harisah; Ria Wikantari; Syarif Beddu; Mohammad Mochsen Sir; Yahya Siradjuddin; Nasruddin Nasruddin; Nurmaida Amri; Imriyanti Imriyanti; Taufik Ishak; Yusaumi FRT (Faculty of Engineering UNHAS, 2021)
Quality houses, facilities and infrastructure are basic needs. To achieve this, it is necessary to formulate a program that is directed, simple, inexpensive, and easy to implement. The results of the visit to the location before the socialization showed that the waterfront settlements of Cikoang in Mangarabombang District, Takalar Regency, South Sulawesi had environmental problems such as lack of greening, non-existent used water drainage, and a lot of garbage scattered, but on the other hand it has a beautiful panorama to be a tourist spot. The purpose of this community service activity is to increase public awareness of the importance of improving the quality of the physical environment such as houses, facilities and settlement infrastructure based on community participation through principle of mutual cooperation and suitable for their needs. The method of implementing community service activities is by means of program socialization in the form of strategies formulated by the community service team of the Faculty of Engineering, Department of Architecture, Hasanuddin University to be shown to the officials and village community. Through the socialization with the banner presentation, it is hoped that there will be a change in the way of thinking from dependence on the government for environmental improvement to the sharing of the burden because of the participation of the community itself, both individually and in groups. This is important to make joint progress in improving the quality of houses, facilities and settlement infrastructure in these locations.